Genome-wide analysis to detect multi-drug resistance genes in Mycobacterium tuberculosis strains SWLPK and MNPK resourced from Pakistan - Maria Rafique; Muhammad Ibrahim; Sumaira Kanwal; Habib Bokhari; Farrukh Jamil; Annam Hussain; Muhammad Asif Rasheed (International Journal of Applied and Experimental Biology)
Development of multidrug-resistant tuberculosis is the after effect of various mutational occasions, which leads to the development of protection from hostile to multiple tuberculosis drugs. In this study, we identified drug resistance genes, their evolutionary analysis, mutational variation, and docking to characterize the drug target potentials of two Mycobacterium tuberculosis strains SWLPK and MNPK resourced from Pakistan. For this purpose, we used different bioinformatics tools including the RAST server for annotation, and UniProt, NCBI, BLAST and MUSCLE for data retrieval and analysis. Evolutionary relationships were drawn using MEGA 7. A 3D structure was modelled by I-TASSER, while refinement and minimizations were performed using the UCSF Chimera 1.14.1. Moreover, the Ramachandran plot was used to check the quality of the proteins, while PatchDock was used for the docking analysis. Based on the comparison with the reference genome (M. tuberculosis H37RV), the SWLPK and MNPK strains encoded 24 multi-drug resistance genes. The drug resistance genes of nearby strains had developmental relatedness and comparable useful attributes imperative to their ecological specialties. The docking analysis revealed that the proteins accurately bound at their binding region just like the reference protein H37Rv (NuoG). We identified 24 multi-drug resistance genes in the SWLPK and MNPK strains. Moreover, there were a few missing drug resistance genes found in H37Rv, which were not present in the MNPK and SWLPK strains. The 24 genes reported in the MNPK and SWLPK strains might have a major contribution in drug resistance.